Oral health policies in Brazil - Gilberto Alfredo Pucca Junior; José Felipe Riani Costa; Luciana de Deus Chagas; Rosa Maria Sivestre (Sociedade Brasileira de Pesquisa Odontológica, 2009)
Since Oral Health policies in Brazil have been constructed according to circumstances and possibilities, they should be understood within a given context. The present analysis contextualizes several issues of the Brazilian Oral Health Policy, called "Smiling Brazil", and describes its present stage of development. Today it involves re-organizing basic oral health care by deploying Oral Health Teams within the Family Health strategy, setting up Centers of Dental Specialists within an Oral Health network as a secondary care measure, setting up Regional Laboratories of Dental Prosthesis and a more extensive fluoridation of the public water supply.